Mechanical characterization of a masonry system made of alkaline activated pozzolana blocks - Salirrosas J. (2020)
The development of alkaline activated materials has enabled the production of eco-friendly alternatives for the construction industry. In the present article, the mechanical characterization of a new structural masonry system composed of fiber-reinforced lightweight pozzolana-based blocks and cement-lime mortar was performed. The mechanical characterization involved uniaxial compression tests in prisms and diagonal compression in wallets. The results indicate that the compressive and shear strength of the masonry system is up to 3.24 MPa and 0.38, respectively. The results obtained indicate that the evaluated system is structurally efficient and that can be used as both non-load and load-bearing walls. © 2020 Trans Tech Publications Ltd, Switzerland.